Note to the Executive Boards of the IMF and the World Bank on the Revised Basel Core Principles for Effective Banking Supervision. (Policy Papers; Policy Paper ;, 2007)
The purpose of this note is to inform the Executive Boards of the World Bank and the IMF of the main changes in the Basel Core Principles and assessment Methodology.